The roots of terrorism - Richardson, Louise 1958- Hrsg (Democracy and terrorism, 2006)
The roots of terrorism : an overview / Louise Richardson -- The psychological dynamics of terrorism / Jerrold M. Post -- Suicide terrorism / Nasra Hassan -- Democracy and terrorism / Leonard Weinberg -- Counterterrorism and repression / Michael Stohl -- Revolutionary terrorism and the state / Ignacio Sanchez-Cuenca -- Economic factors / Ted Robert Gurr -- Terrorism and globalisation / Atanas Gotchev -- Diasporas and terrorism / Gabriel Sheffer -- Religion as a cause of terrorism / Mark Juergensmeyer -- Terrorism and the rise of political Islam / John Esposito -- Terrorism and deculturation / Olivier Roy